Business cultures around the world : a practical guide - Henry, Erwan (Presses universitaires de Grenoble, 2019)
You are in the front line of the Global Economy, you export to Thailand or India, you source from Poland or Mexico, you run a project in Saudi Arabia or Russia, you provide support to Brazilian or Swedish colleagues, you negotiate with German or Korean partners, you struggle to adjust to your French or Chinese employees, you wonder how to be on the same wave length with an American or Japanese boss. You have an international meeting tomorrow and wonder how to meet your objectives? Read the related pages of Business cultures across the world: this practical guide will provide you with the clues to understand your interlocutors and anticipate their reactions. You will find the proper and efficient way to get things done, gain time and raise efficiency, and reduce the risk of misunderstanding and tension.